Identification of vectors of plasmodium knowlesi and other malaria parasites, and studies on their bionomics in Kapit, Sarawak, Malaysia - Tan, Cheong Huat (Universiti Malaysia Sarawak, (UNIMAS), 2008)
The aims of this project were to identify the vectors of P. knowlesi and other malaria parasites in Kapit and to study their bionomics. A one year entomological study was undertaken with three areas chosen as adult mosquito collection sites; a longhouse, where indoor and outdoor collections were undertaken, a farm and the forest, where an elevated platform for money bait trap was also built. The methods of collection were the bare-leg catch and the monkey baited-net trap.